IN SILICO HOMOLOGY SEQUENCE ANALYSIS OF PHOSPHATASE GENES CLONED FROM ASPERGILLUS FUMIGATUS - NEELAKANTAN SURESH,; ARUNAVA DAS, (International Journal of Pharma and Bio Sciences, 2015)
This research work reports the homology modeling of acid phosphatase, phytase and alkaline phosphatase genes of Aspergillus fumigatus. Since soil is a reservoir for the isolation of such fungi, soil microbes were screened for phosphatases and a strain of Aspergillus fumigatus was isolated. A typical fungal colony was isolated after serial dilution, identified as A. fumigatus was used in this study. On molecular identification, the strains identified on the basis of morphological and physiological features were confirmed to belong to A. fumigatus. Their ITS1-ITS4 sequences were up to 99% homologous to reference strains of A. fumigatus from the GenBank. Acid phosphatase, alkaline phosphatase and phytase cDNAs were synthesized from Aspergillus fumigatus RNA by PCR reactions using primers (designed from published NCBI sequences) with reverse transcriptase. This resulted in amplicons corresponding to the predicted gene size of the respective enzymes. They were cloned into bacteria and were subjected to automated DNA sequencing. DNA sequencing after plasmid isolation revealed that the entire nucleotide sequence of the alkaline phosphatase, acid phosphatase and phytase genes from genomic DNA of A. fumigatus was 99.9 % similar to NCBI sequences of Aspergillus fumigatus. The closest homolog to alkaline phosphatase gene of A. fumigatus was Neosartorya fumigata and Neosartorya fumigata. The closest homolog to acid phosphatase gene of A. fumigatus was Neosartorya fischeri. The closest homolog to phytase gene of A. fumigatus was Neosartorya fumigata.